The Effect of Mindfulness Implementation on the Concentration Ability of Early Childhood - Milna Juwita; Syamsuardi; Tasrif Akib; Arie Martuty; Intisari; Nur Alim Amri (Universitas Pendidikan Ganesha, 2025)
Young children often have difficulty concentrating and are easily distracted, which hinders their learning and cognitive development. According to Piaget's theory, the concentration of 5- to 6-year-olds is influenced by their ability to shift their attention. This study aims to evaluate the effect of implementing mindfulness on improving concentration in young children. Mindfulness is defined as a full awareness approach that involves activities such as breathing exercises, meditation, and environmental observation. The study uses a pre-experimental method with a